2016
DOI: 10.1097/brs.0000000000001399
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Scoliosis in Females With Rett Syndrome

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 29 publications
5
63
3
Order By: Relevance
“…21 We have previously observed that, compared with those unable to walk, maintenance of walking skills is associated with less marked progression of scoliosis. 3 Extending our understanding for those with walking skills, scoliosis had little relationship with the amount of activity. However, more frequent seizures had a detrimental effect on activity, possibly in relation to reduced energy levels following seizures or side effects from antiepileptic medications such as lethargy, sleepiness, and poor balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 We have previously observed that, compared with those unable to walk, maintenance of walking skills is associated with less marked progression of scoliosis. 3 Extending our understanding for those with walking skills, scoliosis had little relationship with the amount of activity. However, more frequent seizures had a detrimental effect on activity, possibly in relation to reduced energy levels following seizures or side effects from antiepileptic medications such as lethargy, sleepiness, and poor balance.…”
Section: Discussionmentioning
confidence: 99%
“…1 Seven follow-up questionnaires have been administered between 1996 and 2012 to families and carers of registered cases. 3 In 2012, families whose daughters could walk independently or with assistance, as indicated in the database, were invited to participate in this exploratory study. Longitudinal questionnaire data were interrogated to identify whether scoliosis or epilepsy had been diagnosed or not, and seizure frequency was extracted from the 2012 follow-up questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Growth and nutritional issues are frequently encountered in RTT and require close monitoring and aggressive support [16,20]. Orthopedic issues are also common, with scoliosis occurring in approximately 85% of affected girls and requiring surgical stabilization in 13% [22,23]. Highly prevalent related issues are bone health (i.e.…”
Section: Rtt Diagnosis Clinical Features and Managementmentioning
confidence: 99%
“…Recovery of ambulation skills was more likely for those walking independently than with those who required assistance to walk being vulnerable to losing this skill, regardless of the mode of orthopaedic management. Assisted ambulation has been associated with a gentler trajectory of scoliosis compared with those unable to walk (Downs et al ) and is associated with benefits for quality of life (Epstein et al ). The development of clinical strategies that prevent avoidable loss of assisted ambulation is an important topic of future research.…”
Section: Discussionmentioning
confidence: 99%